Exploiting Slow Dynamics Effects for Damage Detection in Concrete - Bentahar, Mourad; Di Bella, Angelo; Mechri, Charfeddine; Montresor, Silvio; Scalerandi, Marco; Yu, Xiaoyang (Frontiers in Built Environment, 2020)
Nonlinear ultrasonic techniques have been developed in the last decades to detect the presence of damage in materials of interest in the field of civil engineering, such as concrete or mortar. Different approaches have been proposed, exploiting the dependence on the strain amplitude of measurable quantities, such as wave velocity, damping factor, resonance frequency, etc. They have the advantage with respect to linear ultrasonic testing procedures of being much more sensitive to the presence of small variations in the sample microstructure, hence more adapt to detect the presence of small cracks or damaged areas. On the contrary, they usually require a calibrated experimental set-up working in the linear regime when using high amplitude excitations. The slow dynamics features typical of the hysteresis generated by damage have been given much less attention as a tool for damage detection even though their quantification is often less demanding in terms of experimental set-up. Here, we give a first evidence of how recovery, which is part of the slow dynamics process, is sensitive to the presence of damage in concrete samples and thus could be considered as an easy-to-measure nonlinear indicator for Structural Health Monitoring purposes.